Use of prolonged-acting fertilizers in growing garden strawberry seedlings - S. V. Akimova; A. E. Matsneva; L. A. Marchenko; A. V. Solovyov; A. V. Zubkov; A. E. Bulanov; D. S. Arkaev (Овощи России)
Timeliness. Currently, the Russian Federation has a high demand in healthy planting material of garden strawberries. The benefits of using fertilizers when growing strawberry seedlings have been proven by numerous studies. However, a comparative study of the effect of new fertilizers and methods of their application is very limited. In this regard, studies aimed at identifying the effectiveness of the use of prolonged-acting fertilizers in the production of garden strawberry planting material in protected soil conditions are relevant.Methods. Adapted to non-sterile conditions, ex vitro healthy garden strawberry plants were planted in a peat substrate of Veltorf LLC (recipe No. 5c/2) with the addition of Pg mix starter fertilizer with the structure NPK 14-16-18 + microelements (1.5 g/l of substrate). At the same time, prolonged-acting fertilizers were introduced into the substrate in the recommended concentrations: FertiPro Gran 1M (1.25 g/l of substrate), Ruscote 5-6M (3.0 g/l of substrate), Basacote Plus 6M (4.0 g/l of substrate), control peat substrate without fertilizers, PG mix standard.Results. It has been established that for the Karmen crop with an average runner-forming ability, the effectiveness of applying FertiPro Gran 1M fertilizer to the substrate was revealed, with the use of which, on the 180th day of cultivation, the number of runners and rosettes increases by 3.5–3.8 times compared to the control. At the same time, the yield of marketable seedlings is 95% compared to 70% in the control. For the Jūnija smaids crop with a high vine-forming ability, the effectiveness of all experimental variants with the application of FertiPro Gran 1M, Ruscote and Basacote Plus fertilizers to the substrate was revealed, with the use of which, on the 180th day of cultivation, the number of runners and rosettes increases by 1,9-2,5 times compared to the control. At the same time, the yield of marketable seedlings is 94-96% compared to 65% in the control.Conclusion. The introduction of long–acting fertilizers FertiPro Gran, Ruscote and Basacote Plus into the peat substrate with the addition of Pg mix starter fertilizer allowed a 2.3 – 3.8-fold increase in the number of runners obtained and 1.9-3.5-fold increase in the number of sockets obtained compared to the control without fertilizers.